The Effect of Good Corporate Governance and Company Size on Food and Beverage Company Financial Performance - Rizky Adi Baskara; Nursiam (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the effect of good corporate governance (GCG) on financial performance, with GCG proxied by the board of commissioners, independent commissioners, managerial ownership, audit committee, and company size—each selected based on their theoretical roles in enhancing oversight, aligning interests, and ensuring transparency. The research focuses on 58 food and beverage manufacturing companies listed on the Indonesia Stock Exchange during 2020–2022, selected through purposive sampling. Using multiple linear regression, the results show that while the board of commissioners, independent commissioners, managerial ownership, and audit committee do not significantly impact financial performance, company size has a significant positive effect. The sector-specific focus limits generalizability, as governance practices and financial dynamics may differ in other industries.